Analysis and Evaluation of the Knowledge Management - Stredakova, Dana (Communications - Scientific letters of the University of Zilina, 2007)
There is a huge amount of knowledge in any organization. People at all levels have accumulated knowledge about what customers want, about how best to design products and processes, about what has worked in the past and what has not. A company that can collect all that knowledge and share it between employees will have a huge advantage over an organization that never discovers what its people know. Organizations must pay much more attention to the incentives that key workers have to share knowledge, and not focus only on developing the mechanisms that enable them to do so.